Estimation of economic wellbeing at falling price per barrel of oil; Advances in Computer Science Research; Vol. 51 : Information Technologies in Science, Management, Social Sphere and Medicine (ITSMSSM 2016) - Zhdanova A. B. Anna Borisovna; Bannova K. A. Kristina Alekseevna; Dolgikh I. N. Irina Nikolaevna; Kamenskaya K. Y. Kseniya Yurjevna; Pokrovskaia N. V. Nataljya Vladimirovna (2016, 2016)
Title screen